Birds Eye View : Dancing With Martha Graham And On Broadway - Bird, Dorothy, 1912-1996 (Book collections on Project MUSE., 1997)
Bird's Eye View is a warm and human story that chronicles the early development of modern dance from a dancer's perspective. Dorothy Bird was the only dancer of her time to work with all the major choreographers in concert and on Broadway: George Balanchine, Agnes de Mille, Doris Humphrey, Helen Tamiris, Anna Sokolow, Herbert Ross, Jose Limon, and Jerome Robbins, among others. She recounts fascinating theater experiences with such luminaries as Orson Welles, Gertrude Lawrence, Carol Channing, Danny Kaye, and Elia Kazan. Dorothy shares her methods and experiences as a teacher for Balanchine and her twenty-five-year tenure at the Neighborhood Playhouse to highlight her philosophy of "giving back" to the next generation of performers. Of all the artists Dorothy Bird worked with, Martha Graham figures most strongly in the book and in her life. Her narrative about Graham's early creative process is a valuable addition to the literature, as is the story of her personal involvement with Graham. The reader gains an intimate insight into the love and fear instilled by Graham in her followers.